If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x+3)-4=7x+2
We move all terms to the left:
4(x+3)-4-(7x+2)=0
We multiply parentheses
4x-(7x+2)+12-4=0
We get rid of parentheses
4x-7x-2+12-4=0
We add all the numbers together, and all the variables
-3x+6=0
We move all terms containing x to the left, all other terms to the right
-3x=-6
x=-6/-3
x=+2
| 2x/3+3=9 | | -7(a+2)-4=24-a | | 3m(3+8)=m | | -14x-18=15 | | 6(u-3)=-7u+34 | | 9x-6=10x-10 | | 8c=$60.00 | | 8x-1=4x+1 | | 4(4x-9)=2(8x+6) | | 18=2x-7 | | n/0.4=0.08/5 | | 5/8c=145 | | -1/2(p=2)=-3-p | | 3(x-5)=5(x-4) | | 3/5r=21 | | p-3(4+4p)=-78 | | .66x=6/4 | | 3(x^2)-62x-240=0 | | 17x+19=-3 | | 4/5r=7.75 | | -4x-13=9 | | 2(4x-7)=-15 | | 2(4x-7=-15 | | n/25=20/100 | | 84=-6(2-4r) | | (x+4÷8)=(7÷4)+(x-8÷5) | | -(4y+4)-(-3y-5)=-3 | | 34=−2x | | 130=(x+101)+(x+35) | | 3t-t^2-2=0 | | 1/3(21−3a)=6−a | | n/0.4=0.02/10 |